Pheochromocytoma as a Rare Hidden Cause of Inverted Stress Cardiomyopathy - Cho, Soo Kyung (Korean Society of Echocardiography, 2014)
Stress cardiomyopathy (SCMP) is characterized by a transient left ventricular dysfunction associated with apical ballooning and compensatory hyperkinesias of the basal segments after emotional or physical stress, but inverted or mid-ventricular variants of SCMP have also been described. Although catecholamine excess has been suggested as a possible pathophysiologic mechanism of SCMP, the etiology of SCMP is still unknown. Here, we report a case of inverted type of SCMP with clinical presentation mimicking acute coronary syndromes. The cause or precipitating stressor was unclear initially, but pheochromocytoma has been demonstrated as a cause of SCMP during clinical follow-up at out-patient clinic in the present case. Catecholamine-producing tumors should be included in the evaluation or management of SCMP, even though initial clinical manifestations are not suggestive for pheochromocytoma.